Food Heritage and the Construction of Territory: Home-grown products in Québec - Turgeon, Laurier (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2014)
In the Western academic tradition, tangible cultural heritage (monuments, buildings, sites and material objects) has generally been considered as a privileged means of constructing places and territory, whereas intangible cultural heritage (oral traditions, arts, crafts, feasts, rituals, song, music, dance) have been associated with the identification of ethnic groups. This article aims to demonstrate that intangible cultural heritage can also be a powerful means of the construction of place, through a case study that shows how the consumption of home-grown agricultural products in Quebec transforms territories into places of heritage. This transformative process is accomplished, first, by the symbolic production and consumption of place. By clearly identifying the place of origin of the product on the label, in writing as well as in image, the act of eating homegrown products entails a displacement of territory from their place of production to their place of incorporation. The distant and the faraway are brought home and made familiar. To further reinforce the domestication of place, the consumer is invited to come and purchase the homegrown product at the place of production and to bring it back home with him. Second, these places are heritagitized through the social production and consumption of time. Homegrown products are expressions of the continuity of place through the material conservation of food (dehydration, salting, freezing, etc.), the process of ageing itself and, more importantly, the transmission of their intangible qualities (traditional knowledge, transmission of receipts, preservation of taste). These practices become specific to a place to the point that they give the product a distinctive taste that is passed on from generation to generation. It is through taste that the memory of people and place is reactivated. The author of the article further suggests that it is these intangible elements which most efficiently and forcefully express the heritage of place.